Anti-inflammatory and antioxidative effects of thiamin supplements in patients with gestational diabetes mellitus. (3rd June 2022) - Amirani, Elaheh; Aghadavod, Esmat; Shafabakhsh, Rana; Asemi, Zatollah; Tabassi, Zohreh; Panahandeh, Ida; Naderi, Fatemeh; Abed, Alireza
Abstract: Objective: The aim of this study was to evaluate the effects of thiamin supplementation on biomarkers of inflammation and oxidative stress in patients with gestational diabetes mellitus (GDM). Methods: This randomized, double-blind, placebo-controlled trial was conducted among 60 patients with GDM. Patients were randomly allocated into two groups to receive either 100 mg/day thiamin supplements ( n = 30) or placebo ( n = 30) for 6 weeks. Results: Thiamin supplementation significantly decreased serum high-sensitivity C-reactive protein (hs-CRP) ( β − 0.98 mg/L; 95% CI, −1.54, −0.42; p = .001) and plasma malondialdehyde (MDA) levels ( β − 0.86 µmol/L; 95% CI, −1.15, −0.57; p < .001) when compared with the placebo. In addition, thiamin supplementation downregulated gene expression of tumor necrosis factor-alpha (TNF-α) ( p = .002) in peripheral blood mononuclear cells of patients with GDM. Thiamin supplementation did not affect other biomarkers of inflammation and oxidative stress. Conclusion: Overall, thiamin supplementation for 6 weeks to patients with GDM significantly reduced hs-CRP and MDA levels, and gene expression of TNF-α, but did not affect other biomarkers of inflammation and oxidative stress. Clinical trial registration number: Clinical Trials.govIdentifier no. http://www.irct.ir: IRCT20170513033941N58.